Hydro-Engineering Dynamics of Groundwater Rise and Urban Waterlogging in Arid Environments: An Integrated Review and Case Study of Sokna City in Libya - Mohmed Ahmed Yami; Gazala Sanusi Yami (African Journal of Advanced Pure and Applied Sciences, 2026)
Groundwater rise in arid urban environments poses a critical hydro-engineering challenge with serious consequences for infrastructure integrity, public health, and environmental sustainability. This study presents a field-based investigation of groundwater rise and waterlogging in Sokna City, Aljufra district, central Libya, a hyper-arid setting characterized by complex carbonate–argillaceous stratigraphy and severely deteriorated water and sewage infrastructure. The monitoring programmed spanned five months (March–July 2025), deliberately selected as the post-winter recharge window during which groundwater flooding and swamp formation reach their annual maximum in the Aljufra hydro climatological regime. Biweekly depth measurements at ten representative swamp sites documented cumulative water-table rise exceeding (100cm) during the April recharge peak, followed by evaporation-driven recession through July. A critical field observation was the identification of a perennial lake exhibiting year-round waterlogging, independent of seasonal rainfall interpreted as evidence of sustained anthropogenic recharge from chronic infrastructure leakage, and designated as the priority site for a future full-year monitoring programmed. Hydrogeological analysis confirmed that a compound low-permeability sequence of compact Miocene limestone overlying expansive clay generates perched aquifer conditions sustaining surface waterlogging across the urban fabric. A three-layer Hydro-Engineering Interaction Framework (HEIF) is developed integrating recharge inputs, subsurface hydraulic constraints, and surface hydrological manifestations. Engineering recommendations include dimensioned subsurface drainage alignments at (1.5–2.0m) depth, targeted network rehabilitation to reduce non-revenue water losses from ( 40% to below 15%), and mandatory foundation waterproofing standards. Findings are contextualized within the Libyan national experience, with explicit comparison to the Zliten waterlogging case.